Hydrogen adsorption behavior of graphene above critical temperature - Ma, L.P.; Wu, Z.S.; Li, J.; Wu, E.R.; Ren, W.C.; Cheng, H.M.
We evaluate the hydrogen adsorption behavior of the pristine single-layer graphene sheets in a powder form, which was performed at cryogenic and room temperatures. Only 0.4 wt.
Keywords: HYDROGEN STORAGE; PHYSISORPTION; CARBON; GRAPHENE